High temperature interaction of Y4Al2O9/Y2O3 under CMAS exposure: Mechanism of outstanding corrosion resistance through composition design to accelerate reaction-induced CMAS consumption - Jie Li; Luchao Sun; Tiefeng Du; Yang Cui; Jialin Li; Jingyang Wang (Journal of Advanced Ceramics)
The search for new materials with reliable molten calcium–magnesium–alumino–silicate (CMAS) resistance at elevated temperatures is important for the development of advanced aeroengines. In the present study, a novel Y4Al2O9 (YAM)/Y2O3 composite was designed and fabricated from dense samples via the hot-pressing method. The interactions and mechanisms between the Y4Al2O9/Y2O3 composite and CMAS at 1300 and 1500 °C for durations of 1, 4, 25, and 50 h were thoroughly explored. The results revealed that Y4Al2O9/Y2O3 exhibited substantial resistance to CMAS infiltration at both temperatures, without notable grain-boundary penetration by CMAS glass. More importantly, the incorporation of reaction-active components in the composite accelerated the consumption of molten CMAS constituents and reduced their corrosive activity, which is recognized as the crucial principle for the composition design of anti-CMAS materials. This work provides valuable insights that can guide the design of the composition and advancement of superior CMAS-resistant materials.